2016
DOI: 10.1007/s00394-016-1235-8
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between ApoA2 −265T>C polymorphism and dietary fatty acids intake on oxidative stress in patients with type 2 diabetes mellitus

Abstract: The current study shows the interaction between APOA2 polymorphism and dietary fatty acids intake on oxidative stress. More investigations on different populations are required to confirm the interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…Also, to prevent and control the progression of diabetes complications in this genotype group, other effective strategies and programmes are needed. In this regard, two studies have shown that higher intake of anti-inflammatory fatty acids, such as n -3 PUFA and MUFA could compensate for inflammatory effects caused by low plasma level of Apo A-II in CC genotype (83,84) . Studies have shown that dietary intake of W3 fatty acids, like antioxidants, inhibits inflammation, with the difference that, antioxidants exert this anti-inflammatory effect by inhibiting nuclear factor-κB and W3 fatty acid by inhibiting toll-like receptor (85) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, to prevent and control the progression of diabetes complications in this genotype group, other effective strategies and programmes are needed. In this regard, two studies have shown that higher intake of anti-inflammatory fatty acids, such as n -3 PUFA and MUFA could compensate for inflammatory effects caused by low plasma level of Apo A-II in CC genotype (83,84) . Studies have shown that dietary intake of W3 fatty acids, like antioxidants, inhibits inflammation, with the difference that, antioxidants exert this anti-inflammatory effect by inhibiting nuclear factor-κB and W3 fatty acid by inhibiting toll-like receptor (85) .…”
Section: Discussionmentioning
confidence: 99%
“…Rs5082, located in the promoter region of apolipoprotein A2 ( APOA2 ) gene, has been shown to interact with dietary fatty acid intake to modulate inflammation [34,35], and is associated with both lower transcription rate and lower concentration of Apolipoprotein A-II in plasma [36], conferring higher risk of obesity and diabetes mellitus [37,38]. Furthermore, non-T subjects with high omega 3 PUFA intake show greater capacity for oxidative stress neutralization, whereas T carriers have been associated with resistance to increase superoxide dismutase 2 (SOD2) activity with omega 3 PUFA intake [39] and also with an increase in plasma oxidative biomarkers when they present a rich omega 6 PUFA diet [39].…”
Section: Methodsmentioning
confidence: 99%
“…The total antioxidant capacity (TAC) of serum was measured by spectrophotometry. TAC measurement evaluates the overall power of all antioxidants in the body (21,22) Serum enzymatic activity of superoxide dismutase (SOD), as an enzymatic antioxidant ( 22) was estimated by colorimetric method (Cayman Chemical Company, USA). Interleukin-18 (IL-18), Pentrexin-3 (PTX3), and 8-isoprostane F2α (PGF2α) were measured using ELISA method (Shanghai Crystal Day Biotech Co., Ltd).…”
Section: Biochemical Assessment and Genotypingmentioning
confidence: 99%